Analisis Faktor Internal dan Eksternal yang Mempengaruhi Kepatuhan Wajib Pajak UMKM di Kabupaten Buleleng - Luh Ria Wahyuni; I Gusti Ayu Purnamawati (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
This study aims to determine the internal and external factors that affect the tax compliance of micro, small and medium enterprises (MSMEs) in Buleleng regency. This research is a type of quantitative research with a descriptive approach. The population and sample in this study are MSME taxpayers in Buleleng regency which is registered at KPP Pratama (Tax Office) Singaraja. The sampling method used is simple random sampling technique, with a total sample of 334. The data used in this study are primary data obtained by distributing questionnaires to MSME owners. Furthermore, the data collected was tested by multiple linear regression analysis.This research provides the result that awareness does not have a significant positive effect on taxpayer compliance, then tax sanctions, service quality, taxation system modernization, and risk preferences partially have a significant positive effect on taxpayer compliance, while understanding tax and money ethics partially has a significant negative effect on tax compliance.